FENOMENOLOGI KOMUNIKASI ANTAR PRIBADI ORANG TUA DAN ANAK TUNAGRAHITA DALAM MENDORONG MOTIVASI BELAJAR - Marcelina Wehelmina (2023)
People are used to communicating with the same people in the sense that physically and psychologically it can be said to be normal. Limited knowledge about how to communicate with people with disabilities, especially mentally retarded, makes people not understand how to start communicating. So the researchers hope that with this research, people can be aware of the presence of mental retardation so they understand how to communicate with children with special needs such as mentally retarded. This raises the curiosity of researchers about how the experience of interpersonal communication is intertwined between parents who have mentally retarded children. Phenomenology was chosen to know and explore the meaning and experience of the phenomena that occur. The questions posed by the researchers were (1) How do parents interpret the interpersonal communication experiences of parents and mentally retarded children at SLBN 4 Jakarta in encouraging learning motivation (2) What is the experience of interpersonal communication carried out by parents with mentally retarded children at SLBN 4 Jakarta in encouraging learning motivation. The results of the findings obtained from the parents' experiences are in the form of experiences, namely: repeated provocation, giving equal space and opportunities, gentle treatment, positioning as friends, being persuaded, accompanying, and keeping away from distractions.